The Influence of Growth Mindset, Family Environment, School Field Introduction (PLP), and Student Perception of the Teacher Professional Education Program (PPG) on Interest in Becoming an Economics Teacher in East Java - Bayu Cahyo Aji; Jun Surjanti (Economic Education Analysis Journal, 2026)
Student interest in choosing the economics teacher profession is still relatively low. This problem is proven through pre-research data and unstructured interviews which show that most students do not have a strong interest in working as economics teachers. The low interest is suspected to be influenced by various factors, both from within and outside. This study aims to analyze the influence of Growth Mindset, Family Environment, School Field Introduction (PLP), and Student Perception of the Teacher Professional Education Program (PPG) on interest in becoming an economics teacher in East Java. This study uses a quantitative approach with data collection techniques through questionnaires distributed online. The research sample amounted to 191 S1 Economics Education students class of 2022 from the State University of Surabaya, the State University of Malang, and the University of Jember who were selected using purposive sampling techniques. The research data was analyzed using multiple linear regression. The results of the study showed that partially growth mindset, family environment, introduction to the school field, and students' perception of the PPG program had a positive and significant effect on interest in becoming an economics teacher. Simultaneously, the four independent variables have a significant effect on interest in becoming an economics teacher. These findings suggest that the support of internal and external factors together is needed to increase students' interest in becoming economics teachers.